Pengembangan Media Video Powtoon Berbasis Problem Based Learning (PBL) Pada Pembelajaran Tematik Terpadu di Kelas V SD - Susanti, Nelni (Universitas Sebelas Maret, 2020)
The development of science and technology has now entered the era of interactive communication. The term multimedia is one of the solutions that can be used today. Multimedia is a medium that in its manufacture utilizes a computer and produces a moving image, audio, animation. Learning media is a tool in the teaching and learning process to stimulate the thoughts, feelings, and willingness or skills of the learner so that it can encourage the learning process. powtoon is an innovative and simple online software that can create interesting animations using animated videos. This animation can be used for both private and public use. The use of a typical powtoon is in schools, Problem Based Learning (PBL) is one of the learning models that can help students to improve the skills needed in the current era of globalization. Integrated thematic learning is learning that uses themes in the learning process, where each theme has learning materials that can be linked to one another in various subjects.